Herring roe oil in treatment of psoriasis – influence on immune cells and cytokine network - Petrovic, Aleksandra; Bueide, Ingvild; Tveit, Kåre Steinar; Hallaråker, Hogne; Bjørndal, Bodil; Holmes, Tim D.; Davies, Richard; Brokstad, Karl Albert; Bergum, Brith; Appel, Silke (Frontiers in Immunology, 2023)
Psoriasis is a chronic immune-mediated skin disease with systemic inflammation and comorbidities. Although the disease severity may vary over time, many patients suffer from mild to moderate disease. Often local treatment will be sufficient to control the symptoms, but they may have several side effects. ω-3 polyunsaturated fatty acids have shown promising results in clinical trials with mild-to-moderate psoriasis. We explored the impact of phospholipid bound docosahexaenoic acid and eicosapentaenoic acid in a 3:1 ratio on immune cells and cytokine networks in peripheral blood pf patients with psoriasis. The aim of the present study was to investigate the inter-relation of plasma cytokine levels and severity of the disease in 58 patients, and to explore status of circulating immune cell activity in 18 patients with nonsevere psoriasis before and during herring roe oil supplementation. Plasma concentration of 22 cytokines was measured by Luminex technology and circulatory immune cells were analyzed by multicolor flow cytometry. CCL2 levels decreased over time, and IFN-γR1 increased, possibly related to the action of ω-3 polyunsaturated fatty acids. The observed shift from naïve to effector CD4 + T cells and decreases of CD38 expression on CD4 + and CD8 + T cells, CD56 bright NK cells and CD14 + CD16 -classical monocytes supports the beneficial effect of herring roe oil supplementation.